2009
DOI: 10.1016/j.bone.2009.04.237
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in parathyroid hormone secretion and mineral metabolism in response to oral phosphate administration

Abstract: Ethnic differences in bone metabolism have been reported and it has been suggested that these may be partly due to prolonged exposure to an elevated plasma parathyroid hormone (PTH) concentration or a decreased sensitivity to PTH. We explored ethnic differences in bone and mineral metabolism by 5 days of oral phosphate (P) loading to stimulate PTH secretion. Healthy older people from UK (B), The Gambia (G) and China (C), 15 individuals from each sex and ethnic group, were studied. Blood and urine samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 35 publications
8
37
0
Order By: Relevance
“…A study describing ethnic differences in phosphorus homeostasis was excluded from our review, because results were not presented in an appropriate way. The study showed that phosphorus supplementation influences plasma phosphorus and calcium in a similar way in British, Gambian and Chinese subjects, but secretion of 1,25(OH) 2 D, PTH and excretion of calcium after supplementation differ between ethnicity (Yan et al 2009). Still, in the prospective cohort study of Alonso et al that was included in our review, pooled analysis of data from two prospective cohort studies was stratified for Caucasians and African Americans, but both strata showed similar results: no significant association between dietary phosphorus and hypertension was observed .…”
Section: Bioavailability and Affecting Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study describing ethnic differences in phosphorus homeostasis was excluded from our review, because results were not presented in an appropriate way. The study showed that phosphorus supplementation influences plasma phosphorus and calcium in a similar way in British, Gambian and Chinese subjects, but secretion of 1,25(OH) 2 D, PTH and excretion of calcium after supplementation differ between ethnicity (Yan et al 2009). Still, in the prospective cohort study of Alonso et al that was included in our review, pooled analysis of data from two prospective cohort studies was stratified for Caucasians and African Americans, but both strata showed similar results: no significant association between dietary phosphorus and hypertension was observed .…”
Section: Bioavailability and Affecting Factorsmentioning
confidence: 99%
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. The article does not meet the requirements on conducting a systematic review Whybro, et al 1998 Article included in the review of Williams, et al 1996 No representative population, patients with osteopetrosis Wood, et al 1995 The article does not meet the requirements on conducting a systematic review Yan, et al 2009 Results only presented in figures Yang, et al 1994 No quantifiable information on the amount of phosphorus in the supplement, also calcium supplementation Yang, et al 2011 The article does not meet the requirements on conducting a systematic review The present document has been produced and adopted by the bodies identified above as author(s). This task has been carried out exclusively by the author(s) in the context of a contract between the European Food Safety Authority and the author(s), awarded following a tender procedure.…”
Section: Jones 2011mentioning
confidence: 99%
See 1 more Smart Citation
“…There are ethnic differences in the metabolism of the bone forming minerals, calcium (Ca) and phosphate (P), with differences in renal Ca excretion, even at similar intakes and rates of absorption. We have previously reported a lower urinary Ca excretion in Black Gambian (G) compared to Caucasian British (B) subjects (1) . These ethnic groups are known to differ in their dietary Ca intake and vitamin D (VD) status.…”
mentioning
confidence: 99%
“…Anthropometry was performed. Blood ionised Ca (iCa), plasma (p) total Ca (pCa), P (pP), 25-hydroxy VD (25VD), 1,25-dihydroxy VD (1,25VD), parathyroid hormone (PTH), and urinary (u) Ca (uCa), creatinine (uCr), and uP were analysed (1) . The fractional excretion of Ca (FECa) and the tubular maximum of Ca (TmCa) were calculated (2) .…”
mentioning
confidence: 99%